Coexistent Pseudogout and Mycobacterium avium-intracellulare Septic Arthritis in a Patient with HIV and ESRD - Wais Afzal; Omer M. Wali; Kelly L. Cervellione; Bhupinder B. Singh; Farshad Bagheri (Case Reports in Rheumatology)
Pseudogout is a crystal-induced arthropathy characterized by the deposition of calcium pyrophosphate dihydrate (CPPD) crystals in synovial fluid, menisci, or articular cartilage. Although not very common, this entity can be seen in patients with chronic kidney disease (CKD). Septic arthritis due to Mycobacterium avium-intracellulare (MAI) is a rare entity that can affect immunocompromised patients such as those with acquired immunodeficiency syndrome (AIDS) or those who are on immunosuppressive drugs. Here, we describe a 51-year-old female who presented with fever, right knee pain, swelling, warmth, and decreased range of motion for several days. The initial assessment was consistent with pseudogout, with negative bacterial and fungal cultures. However, due to high white blood cell (WBC) count in the synovial fluid analysis, she was empirically started on intravenous (IV) vancomycin and piperacillin-tazobactam and discharged on IV vancomycin and cefepime, while acid-fast bacilli (AFB) culture was still in process. Seventeen days later, AFB culture grew Mycobacterium avium-intracellulare (MAI), and she was readmitted for relevant management. This case illustrates that septic arthritis due to MAI should be considered in the differential diagnosis of septic arthritis in immunocompromised patients.